2018
DOI: 10.1126/scitranslmed.aap9527
|View full text |Cite
|
Sign up to set email alerts
|

A protective Langerhans cell–keratinocyte axis that is dysfunctional in photosensitivity

Abstract: Photosensitivity, or skin sensitivity to ultraviolet radiation (UVR), is a feature of lupus erythematosus and other autoimmune and dermatologic conditions, but the mechanistic underpinnings are poorly understood. We identify a Langerhans cell (LC)-keratinocyte axis that limits UVR-induced keratinocyte apoptosis and skin injury via keratinocyte epidermal growth factor receptor (EGFR) stimulation. We show that the absence of LCs in Langerin-diphtheria toxin subunit A (DTA) mice leads to photosensitivity and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 54 publications
(88 reference statements)
14
55
0
Order By: Relevance
“…The commonly upregulated pathways included different forms of cell adhesions (focal, adherent and tight)-, ribosome and RNA biogenesis-, autophagy-, bacterial invasion/infection-, MAPK-and ErbB signaling pathways (Fig 2D). Alterations in adhesion molecules and the ErbB signaling pathway in KCs, in the absence of LCs, were recently reported [24,33]. The downregulated pathways showed considerably less overlap between these two cell types and included some of the amino acid degradation pathways ( Fig 2D).…”
Section: The Absence Of Lcs Affected a Variety Of Different Cellular supporting
confidence: 61%
“…The commonly upregulated pathways included different forms of cell adhesions (focal, adherent and tight)-, ribosome and RNA biogenesis-, autophagy-, bacterial invasion/infection-, MAPK-and ErbB signaling pathways (Fig 2D). Alterations in adhesion molecules and the ErbB signaling pathway in KCs, in the absence of LCs, were recently reported [24,33]. The downregulated pathways showed considerably less overlap between these two cell types and included some of the amino acid degradation pathways ( Fig 2D).…”
Section: The Absence Of Lcs Affected a Variety Of Different Cellular supporting
confidence: 61%
“…Here, we observed that both local and systemic early production of IFN-I following skin exposure to UVB was almost entirely cGAS dependent. In normal situations, acute inflammation is resolved through many reparative mechanisms that involve T-regulatory cells, Langerhans cells, and anti-inflammatory cytokines such as IL-10 (Shipman et al, 2018;Wolf et al, 2019;Yamazaki et al, 2018). Why SLE patients fail to control the inflammatory response in the skin and elsewhere is a critical question that will benefit from understanding the pathogenetic pathways involved.…”
Section: Remarkably Uvb Exposure Induces a Systemic Ifn-i Response Amentioning
confidence: 99%
“…The commonly upregulated pathways included different forms of cell adhesions (focal, adherent and tight)-, ribosome and RNA biogenesis-, autophagy-, bacterial invasion/infection-, MAPK- and ErbB signaling pathways ( Figure 2d ). Alterations in adhesion molecules and the ErbB signaling pathway in KCs, in the absence of LCs, were recently reported(22,31). The downregulated pathways showed considerably less overlap between these two cell types and included some of the amino acid degradation pathways ( Figure 2d ).…”
Section: Resultsmentioning
confidence: 83%